2019
DOI: 10.1101/869883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective potential reveals evolutionary trajectories in complex fitness landscapes

Abstract: Growing efforts to measure fitness landscapes in molecular and microbial systems are premised on a tight relationship between landscape topography and evolutionary trajectories. This relationship, however, is far from being straightforward: depending on their mutation rate, Darwinian populations can climb the closest fitness peak (survival of the fittest), settle in lower regions with higher mutational robustness (survival of the flattest), or fail to adapt altogether (error catastrophes). These bifurcations h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 73 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…In (33), I showed that continuous-time replicator-mutator (or quasispecies) equations can be understood in terms of a derived Markov process, for which the logarithm of the selection-mutation equilibrium plays the role of an effective potential. With discrete generations, this scheme can be reformulated as follows: Given a discrete space X, consider a sequence of probability distributions p t : X → ℝ evolving under the dynamics p t+1 (x ) = (B p t ) (x)…”
Section: Robustness and Evolvabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In (33), I showed that continuous-time replicator-mutator (or quasispecies) equations can be understood in terms of a derived Markov process, for which the logarithm of the selection-mutation equilibrium plays the role of an effective potential. With discrete generations, this scheme can be reformulated as follows: Given a discrete space X, consider a sequence of probability distributions p t : X → ℝ evolving under the dynamics p t+1 (x ) = (B p t ) (x)…”
Section: Robustness and Evolvabilitymentioning
confidence: 99%
“…3 is not readily interpretable in terms of "evolutionary trajectories." This can be remedied by means of the change of variable q t (x) ∝ S(x)p t (x), where S is the (left) eigenvector of B with largest eigenvalue; by the Perron-Frobenius theorem, this vector is positive and its eigenvalue is the spectral radius  of S. Via this transformation, which only depends on t through a global constant, we obtain a Markovian representation of the original dynamical problem with master equation For this derived process, the function U = − 2 log S plays the role of a potential; its analysis reveals the metastable states and preferred trajectories of the original (nonlinear) process (33,47). The equilibrium distribution for Eq.…”
Section: Robustness and Evolvabilitymentioning
confidence: 99%
“…To understand the limits of neutral evolution in interfering populations we must study the full trajectory p t (x) and not just its asymptotic equilibrium Q (x). For this purpose we can use the framework recently developed in (Smerlak, 2019), which maps the non-linear dynamics 1 onto a Markov chain on G via the change of variables q t (x) ∝ Q(x)p t (x) (SI ). This new distribution satisfies the master equation…”
Section: Equivalence With the Maximal Entropy Random Walkmentioning
confidence: 99%
“…In (Smerlak, 2019) I showed that continuous-time replicator-mutator (or quasispecies) equations can be understood in terms of a derived Markov process, in which the logarithm of the selectionmutation equilibrium plays the tole of an effective potential. With discrete generations, this scheme can be reformulated as follows.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation